Translation and validation of Bristol Female lower urinary tract symptoms (BFLUTS) questionnaire for Nepali speaking women - Thapa, Baburam Dixit; Chandra Regmi, Mohan; Basnet, Tulasa (Journal of Nepal Health Research Council, 2024)
Title: Translation and validation of Bristol Female lower urinary tract symptoms (BFLUTS) questionnaire for Nepali speaking womenIntroduction: Bristol female lower urinary tract symptoms questionnaire (BFLUTS) was designed to identify the lower urinary tract symptoms (LUTS) in women. It aids in determining the severity of lower urinary tract symptoms and how they affect sexual function and quality of life.It can be employed in research and therapeutic practice. It is not available in Nepali version. As a result, our goal is to translate and validate the BFLUTS questionnaire in Nepali.Methods: The BFLUTS questionnaire has been translated into Nepali. From March 1, 2020 to February 28, 2021, 225 Nepalese patients with lower urinary tract symptoms were evaluated using a Nepali version of the BFLUTS questionnaire adapted from the English version. Internal consistency, test-retest reliability, validity, and change responsiveness were all assessed.Results: A total of 225   patients were enrolled in the study. The missing data was less than 2%. The Nepali version of the BFLUTS questionnaire showed good reliability (? = 0.76; ICC= 0.934). Test-retest reliability was assessed with weighted kappa (?) ranging from 0.71 to 0.83.It showed good sensitive to change before and after the treatment. Mean BFLUTS scores correlated strongly with the symptomsof lower urinary tract symptoms reported in the bladder diary with ? ranging from 0.689to 0.859.Conclusions: The Nepali version of BFLUTS questionnaire is a reliable, valid and consistent for measuring lower urinary tract symptoms and their effect on sexual function and quality of life.Keywords: BFLUTS; LUTS; Nepali; Reliability; Validity.